Biostratigraphy of Dammam Formation Succession in Boreholes N2 and S1 in Al-Najaf and Al-Samawa Area - Al-Dulaimi , Salam Ismeal; Al-Wa‘aly , Mohammed Kareem Abdul Hussein (Iraqi Journal of Science, 2022)
The Dammam Formation in S and SW of Iraq is an Eocene carbonate succession consisting of limestone and dolostone. Two boreholes are selected in Al-Najaf and Al-Samawa area to investigate the biostratigraphy. The biostratigraphy of Dammam Formation consist of 22 species which belong to 13 genera of fossils foraminifera.Two biozones were distinguished in Dammam Formation depending on benthonic foraminifera Nummulites. These biozones are; Nummulites gizehensis range zone and Alveolina sp. – Coskinolina sp. assemblage zone. According to thESE biozones the age of Dammam Formation represent Middle Eocene , whereas absent of these biozone represent Early and Late Eocene.